Preparation of particle electrodes from manganese slag and its degradation performance for salicylic acid in the three-dimensional electrode reactor (TDE). (February 2019) - Chen, Hao; Feng, Yan; Suo, Ning; Long, Yingying; Li, Xue; Shi, Yulong; Yu, Yanzhen
Abstract: Salicylic acid (SA) is a class of trace pollutants widely presented in the environment belonged to pharmaceuticals and personal care products. It is difficult to remove SA by the traditional treatment processes because of its toxicity. In this paper, the degradation of SA by Mn-loaded Cu/Fe particle electrodes was studied. Firstly, the particle electrodes were prepared by impregnation-roasting method and then characterized by SEM, XRF and XRD. The diffraction peaks of Fe2 O3 and CuO in the XRD patterns of the particle electrodes which had the dense spherical particles were significantly increased and the content of CuO and Fe2 O3 increased by 1.9% and 3.6% respectively. Secondly, single factor experiments were carried out under conditions of cell voltage, electrolyte concentration, pH, HRT, inter-electrode distance and initial pollutant concentration. Under the optimum conditions of all the factors, the degradation rate of SA reached 76.9%. Then, HPLC and GCMS were employed to deduce the degradation pathways of SA by the TDE with Mn-particle electrodes (Mn-PETDE). Under the action of OH, SA underwent decarboxylation and substitution reactions and then mineralized after the ring-opening reaction. All results demonstrated that this Mn-PETDE was effective for degradation of SA. Highlights: Particle electrodes were used by manganese slag. Getting the optimal condition by single factor experiments. Mn-PETDE had a high efficient degradation performance to salicylic acid. The degradation pathway of salicylic acid was proved through HPLC and GC-MS.